Titel prent: Bebel: Donnerwetter, dát is een tegenslag. En dat net met die Landdagverkiezingen! - Hahn, Albert,
Titel prent: Bebel: Donnerwetter, dát is een tegenslag. En dat net met die Landdagverkiezingen!.